(5x/x-2) - 7 = (10/x-2)

Add 7 to both sides

(5x/x-2) = (10/x-2) + 7

Multiply both sides by (x-2)

5x = 10 + 7x - 14

Simplify

5x = 7x - 4

**X = 2**

However this doesn't satisfy the original equation; we end up dividing by 0. This...

## Unlock

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

(5x/x-2) - 7 = (10/x-2)

Add 7 to both sides

(5x/x-2) = (10/x-2) + 7

Multiply both sides by (x-2)

5x = 10 + 7x - 14

Simplify

5x = 7x - 4

**X = 2**

However this doesn't satisfy the original equation; we end up dividing by 0. This is easier to see in a graph;

Both equations have an asymptote at x=2.

Thus, the solution to this problem is not a specific value of x, because *all* X values are permitted *except *the value 2. Thus we would say that the domain is x `!=` 2, or that a vertical asymptote is located at x=2